Sanksi Pidana Terhadap Tindak Pidana Aborsi (Studi Kasus Putusan Nomor : 87/Pid.G/2007/Pn.Gir) - Bujangga Agus Arif Pranata; I Nyoman Sujana; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2020)
As part of criminal acts, it is a matter of abortion, namely: mainly among women who experience unwanted pregnancies choose the path for abortion with various risks, namely in the form of death or legal violation of the provisions in the Criminal Code. For example, it often happens that a woman intentionally causes death or death of her womb, or tells another person to cause it, she is sentenced to imprisonment for a maximum of four years, which is regulated in the Criminal Code (KUHP). Abortion is a prohibited act, so it is said to be a criminal act, because the threat of partial criminal law is regulated in the Criminal Code. The formulation of the problem in this study is: what is the background of the perpetrator committing an abortion crime and how is the criminal sanction imposed by the judge on the perpetrator of the crime of abortion. The type of research used in this study is normative legal research. The results of the discussion in this study are: The background of the perpetrators committing abortion crimes, namely from unmarried women (too young, girlfriends refusing to be responsible, not planning to marry a boyfriend, fear of parents, maintaining a good family name and tradition) and those who have gotten married (contraceptive failure, is in the process of divorce, and the husband is not responsible). Criminal sanctions imposed by judges on perpetrators of abortion crimes, namely in the Criminal Code, the perpetrators and those who assist in the occurrence of abortion are charged with Article 346 to Article 349.